THE ROLE OF LANGUAGE POLICY IN PROMOTING ECONOMIC DEVELOPMENT - Tursunova Ozodaxon To’raxon qizi; Tursunxo‘jayeva Moxigul Maxmud qizi (Ustozlar uchun, 2025)
Language policy has profound implications for economic development, particularly in multilingual societies. This paper investigates the impact of language policies on education, labor markets, and trade. By analyzing case studies from diverse contexts, the study highlights how inclusive and strategic language policies can foster economic growth, reduce inequalities, and strengthen national cohesion.